Mechanisms of Action of Phytochemicals from Medicinal Herbs in the Treatment of Alzheimerʼs Disease - Kim, Mi Hye; Kim, Sung-Hoon; Yang, Woong Mo (Planta Medica, 2014)
Alzheimerʼs disease is a chronic neurodegenerative disorder characterized by progressive dementia and deterioration of cognitive function. Although several drugs currently used for the treatment of Alzheimerʼs disease delay its onset and slow its progression, still there is no drug with profound disease-modifying effects. Studies aiming the treatment of this neurodegenerative disorder explore various disease mechanisms. Since antiquity, medicinal herbs have been used in traditional medicine. Recent studies suggest that the neurobiological effects of phytochemicals from medicinal herbs may contribute to clinical benefits in in vitro and in vivo models of Alzheimerʼs disease. This review focuses on five phytochemicals, berberine, curcumin, ginsenoside Rg1, puerarin, and silibinin, which have been mostly investigated to treat the development and progression of this neurodegenerative disorder.
Keywords: Alzheimerʼs disease; phytochemical; medicinal herbs; drug development